Penerapan Metode Lean UX pada Pengembangan Aplikasi Bill Splitting menggunakan Platform Android - Ismail Rabbanii; Adam Hendra Brata; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Bill splitting is a way to divide the burden on a bill into two or more parts. Based on the survey conducted on 28 respondents born in one of 1995 to 2014 in Indonesia showed that 64.3% of the total respondents gave grades 3 to 5 on a scale of 1 to 5 regarding how much difficulty they felt when sharing bills. These findings become a reason for researchers to develop an application that can facilitate respondents in sharing bills. This research provides an answer to the problem that has been elaborated by implementing Lean UX as a method of developing user experience on an Android-based bill splitting application called Ezcount. Lean UX is a method of developing user experience that has four stages in the process, namely Declaring Assumptions, Create MVP, Run Experiment, and Feedback & Research. After going through two iterations, usability testing on the application that has been made shows the results on the effectiveness criteria of 92.73%, the efficiency criteria is 92.00%, and the criteria for the user satisfaction level are 85.50%. When calculating the average of the test results, the final value of testing usability of Ezcount application is 90.08%, which can be concluded that the Ezcount application has a very good usability level.